2023
DOI: 10.3390/genes14030715
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Changes in Cancer: Insights on Carcinogenesis and Potential for Non-Invasive Diagnostic Strategies

Abstract: Telomere dynamics play a crucial role in the maintenance of chromosome integrity; changes in telomere length may thus contribute to the development of various diseases including cancer. Understanding the role of telomeric DNA in carcinogenesis and detecting the presence of cell-free telomeric DNA (cf-telDNA) in body fluids offer a potential biomarker for novel cancer screening and diagnostic strategies. Liquid biopsy is becoming increasingly popular due to its undeniable benefits over conventional invasive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 173 publications
0
5
0
Order By: Relevance
“…The maintenance of chromosome integrity heavily relies on telomere dynamics. Alterations in telomere length can potentially contribute to the development of cancer [20]. Leukocyte telomere length is known to be heritable and has been associated with longevity.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of chromosome integrity heavily relies on telomere dynamics. Alterations in telomere length can potentially contribute to the development of cancer [20]. Leukocyte telomere length is known to be heritable and has been associated with longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Telomeres are known to control cell division and cellular death; thus playing a critical role in cell maintenance and chromosome integrity ( Bernadotte et al , 2016 ). Previous studies have shown that TL is a biomarker for various human diseases and pathological conditions such as coronary artery disease ( Sagris et al , 2022 ), diabetic kidney disease ( Hill et al , 2023 ), exposure to air pollution ( Zizza et al , 2022 ), and cancers ( Holesova et al , 2023 ). Furthermore, TL is essential in normal development of the embryo and fetus; thus, the abnormal shortening of telomeres is likely involved in embryo loss during early human development ( Thilagavathi et al , 2013 ; Kohlrausch et al , 2021 ) and is the primary indicator of non-viable fetus elimination ( Huleyuk et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several scholars have suggested that both shorter and longer telomeres may contribute to carcinogenesis, and that an optimal TL represented a balance between cell proliferation, senescence, and control [41][42][43]. Cells with longer TL had greater proliferative and mutational potential, leading to the onset of HODGKIN, while shortened TL was often correlated with disease severity after onset [44,45].…”
Section: Discussionmentioning
confidence: 99%